PEMAHAMAN PESERTA PEMBEKALAN GURU KELAS/AGAMA DALAM MATA PELAJARAN PENJAS TERHADAP PENDIDIKAN JASMANI SD DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Dwi Marhaendro, Agus Susworo (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">The aim of this research is to reveal a description on <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">the participants’ understanding of teaching learning <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">process in elementary physical education on the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">cognitive, affective, and psychomotor aspects. They <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">were the participants of training for classroom/ religion <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">teachers in Yogyakarta Special Province. The <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">population was 80 classroom/ religion teachers who <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">participated in the training of 2005. The sample was <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">60 teachers taken by purposive sampling procedures. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">This research employed descriptive approach using <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">questionnaire as the data collection technique. The <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">results showed that for cognitive aspect, it was 91, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">67% of cognitive aspect categorized as high, 8,33% <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">as medium, and 0% as low. It was 6,7 %of affective <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">aspect categorized as high, 5 % as medium, and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">18,33 % as low. It was 63,33% of psychomotor aspect <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">categorized as high, 36,67% as medium, and 0% as <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">low. The total of those three aspects showed that the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">understanding of the training participants were 43,33% <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">included as high category, 56,67% included as <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 324.05pt; mso-height-rule: exactly;">medium category, and 0% included as low category. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 624.1pt; mso-height-rule: exactly;">Kata kunci: Pemahaman, Guru Kelas/Agama SD, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 624.1pt; mso-height-rule: exactly;">Pembelajaran Pendidikan Jasmani